Programmable trap geometries with superconducting atom chips - Müller, T. (2014)
We employ the hysteretic behavior of a superconducting thin film in the remanent state to generate different traps and flexible magnetic potentials for ultracold atoms. The trap geometry can be programed by externally applied fields. This approach for atom optics is demonstrated by three different trap types realized on a single microstructure: a Z-type trap, a double trap, and a bias-field-free trap. Our studies show that superconductors in the remanent state provide a versatile platform for atom optics and applications in ultracold quantum gases.